The International Dimension of the Brazilian Higher Education System Through the Prism of South-South Cooperation - Brum, José Antonio; Knobel, Marcelo (International Journal of African Higher Education, 2018)
International cooperation is a growing trend among research universities. In the past, this took the form of collaboration between researchers in developing countries with those in the developed world that enjoy superior access to fnancial and technical resources as well as infrastructure. More recently, the collaboration map has begun to change, as scientists in developed countries recognised how local context can aﬀect their work, and those in developing countries are slowly building their research capabilities. Furthermore, South-South research collaboration is considered increasingly important, alongside developments in science and higher education in these countries. Following a brief overview of the Brazilian higher education system, this article discusses the complexity of establishing international collaboration, citing a few programmes aiming at strengthening South-South cooperation. La coopération internationale ne cesse de croitre au sein des universités de recherche. Dans le passé, elle prenait la forme d’une collaboration entre les chercheurs de pays en voie de développement et ceux de pays développés, qui ont accès à des ressources fnancières et techniques ainsi que des infrastructures supérieures. Plus récemment, le format des collaborations a commencé à changer, alors que les scientifques des pays développés reconnaissent la manière dont le contexte local impacte leur travail, tandis que ceux des pays en voie de développement créent doucement des capacités de recherche. Par ailleurs, la collaboration de recherche sud-sud est de plus en plus considérée essentielle, parallèlement aux développements de la science et de l’enseignement supérieur dans ces pays. Après une brève introduction au système d’enseignement supérieur brésilien, cet article aborde la complexité de la mise en place de partenariats internationaux, en faisant référence à quelques programmes visant à renforcer les coopérations sud-sud.